2020
DOI: 10.1101/2020.10.21.348458
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Insect wing extract: A novel source for green synthesis of nanoparticles of antioxidant and antimicrobial potential

Abstract: Silver nanoparticles (AgNPs) are among the most widely synthesized and used nanoparticles (NPs). AgNPs have been traditionally synthesized from plant extracts, cobwebs, microorganisms, etc. However, their synthesis from wing extracts of common insect; Mang mao which is abundantly available in most of the Asian countries has not been explored yet. We report the synthesis of AgNPs from M. mao wings extract and its antioxidant and antimicrobial activity. The synthesized AgNPs were spherical, 40–60 nm in size … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Various parts of plants such as leaves, bark, roots and fruit peels have been used in previous studies 5,14,16 . Additionally, many studies have reported AgNPs synthesis using agricultural waste 17 , enzymes 18 , insects' metabolites 19 , and more interestingly animal wastes 20 as well. Therefore, these biological materials for NPs synthesis are gaining dominancy over chemical or physical methods for AgNPs synthesis.…”
mentioning
confidence: 99%
“…Various parts of plants such as leaves, bark, roots and fruit peels have been used in previous studies 5,14,16 . Additionally, many studies have reported AgNPs synthesis using agricultural waste 17 , enzymes 18 , insects' metabolites 19 , and more interestingly animal wastes 20 as well. Therefore, these biological materials for NPs synthesis are gaining dominancy over chemical or physical methods for AgNPs synthesis.…”
mentioning
confidence: 99%